Digital Technologies and Firms' Employment and Training - Mauro Caselli; Edwin Fourrier-Nicolai; Andrea Fracasso; Sergio Scicchitano (Center for Economic Studies and ifo Institute (CESifo), 2024)
This study examines the causal influence of digital technologies, specifically operational (ODT) and information digital technologies (IDT), on firms' employment structure using Italian firm-level data. It employs a unique empirical approach, constructing instrumental variables based on predetermined employment composition and global technological progress, proxied by patents. Findings indicate that IDT investment positively affects employment, favoring a skilled, IT-competent workforce, as supported by firms' training and recruitment plans. Conversely, ODT investment does not significantly alter total employment but skews the workforce towards temporary contracts. The study contributes methodologically by distinguishing between ODT and IDT and highlighting nuanced employment dynamics within firms.
Keywords: D22; J23; J24; M51; M53; O33; 330; digital technologies; labour demand; training; firms